2014
DOI: 10.1161/circgenetics.113.000398
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Regulates Platelet Function and Contributes to Coagulation Abnormality and Organ Injury in Hemorrhagic Shock and Resuscitation

Abstract: Background Growing evidence indicates that the presence of TLR4 on platelets is a key regulator of platelet number and function. Platelets exposed to TLR4 agonists may serve to activate other cells such as neutrophils and endothelial cells in sepsis and other inflammatory conditions. The functional significance of platelet TLR4 in hemorrhagic shock, however, remains unexplored. Methods and Results Using thromboelastography and platelet aggregometry, we demonstrate that platelet function is impaired in a mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 52 publications
2
43
0
2
Order By: Relevance
“…HMGB1 is known to bind to toll like receptor 4 (TLR4) and stimulate inflammation [54]. Activation of the TLR4 pathway has also been recently implicated in platelet impairment [55]. The early metabolic changes and release of DAMPs following injury are potential mechanisms of platelet ADP inhibition that prime the injured patient for systemic hyperfibrinolysis if they are allowed to progress to hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is known to bind to toll like receptor 4 (TLR4) and stimulate inflammation [54]. Activation of the TLR4 pathway has also been recently implicated in platelet impairment [55]. The early metabolic changes and release of DAMPs following injury are potential mechanisms of platelet ADP inhibition that prime the injured patient for systemic hyperfibrinolysis if they are allowed to progress to hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, high‐mobility group box 1 (HMGB1) has been lately the focus of attention as it is a strong inductor of platelet activation. It appears to be a relevant molecule involved in coagulation abnormalities and organ injury observed in hemorrhagic shock and resuscitation . Additionally, cellular fibronectin containing extra domain A (Fn‐EDA +), which is produced in response to tissue injury in several disease states, has pro‐thrombotic activity, as it interacts with platelet TLR4 and promotes agonist‐induced platelet aggregation .…”
Section: Platelet Tlr4 Activation Promotes Platelet Pro‐thrombotic Anmentioning
confidence: 99%
“…It appears to injury observed in hemorrhagic shock and resuscitation. 27 Additionally, cellular fibronectin containing extra domain A (Fn-EDA +), which is produced in response to tissue injury in several disease states, has prothrombotic activity, as it interacts with platelet TLR4 and promotes agonist-induced platelet aggregation. 28 Interestingly, histones, other DAMPs bound to neutrophil extracellular traps, (NETs) trigger both pro-thrombotic and pro-coagulant platelet-mediated responses, partly by interacting with TLR4 29,31 (Fig.…”
Section: Platelet Tlr4 Activation Promotes Platelet Pro-thrombotic Anmentioning
confidence: 99%
“…Trauma has been shown to result in a release of endogenous danger signals, known as damage associated molecular pattern (DAMP) molecules, which are activators of the innate immune system (42). DAMP signaling through critical innate immune receptors like the Toll like receptors (TLRs) has recently been implicated in the pathophysiology of coagulopathy after trauma (43, 44) and the common thrombotic complications after trauma, such as deep vein thrombosis (45). Ding and colleagues discovered that expression of TLR4 on platelets was necessary and sufficient to regulate sequestration of platelets in the lung following hemorrhagic shock, although the ligand for platelet TLR4 was unknown (43).…”
Section: Pro: Coagulopathy Should Be a Therapeutic Target In Criticalmentioning
confidence: 99%
“…DAMP signaling through critical innate immune receptors like the Toll like receptors (TLRs) has recently been implicated in the pathophysiology of coagulopathy after trauma (43, 44) and the common thrombotic complications after trauma, such as deep vein thrombosis (45). Ding and colleagues discovered that expression of TLR4 on platelets was necessary and sufficient to regulate sequestration of platelets in the lung following hemorrhagic shock, although the ligand for platelet TLR4 was unknown (43). Subsequent studies from the same group revealed that expression release of the endogenous danger signal and TLR4 ligand, high mobility group box 1 (HMGB1), from platelets following trauma in both humans and mice resulted in autocrine and paracrine platelet activation, leading to a phenotype of microvascular thrombosis and lung and liver injury in a murine model of polytrauma and hemorrhage (44).…”
Section: Pro: Coagulopathy Should Be a Therapeutic Target In Criticalmentioning
confidence: 99%